Biological Control of Root-Knot Nematodes Using Local Fungal Isolates and Crop Rotation Strategies in Vegetable Fields - Hbaiel, Mohammad Kareem (American Journal of Biology and Natural Sciences, 2025)
The combination of local fungal fungi (Trichoderma harzianum and Paecilomyces lilacinus) and crop rotations (tomato- marigold-cowpea) was evaluated with the aim of controlling root-knot nematodes (Meloidogyne incognita) sustainably in vegetable fields. This research attempted to find a less chemical-intensive alternative to the use of nematicides and improve soil quality and yield of crops. methods: A randomized complete block design with 8 replications included four treatments as follows: (1) untreated control, (2) fungal application, (3) crop rotation, and (4) fungi and crop rotation together. The population of nematodes, galling index, the development of plants, and microbial soil activity (FDA hydrolysis) was followed across the complete growing cycle. Results: The integrated therapy reduced levels of nematodes by 68.5 percent, which is much higher than fungal-only (26.8 percent) and rotation-only (37.2 percent) techniques. It also increased vegetable production by 69% compared with the control, with the lowest galling index (1.1 as compared to 9.0 in the control). The health of the soil was greatly improved as the microbial activities went up twice (25.6 vs. 12.4 9g FDA/g soil/h) and the organic matter increased by 38 percent in the plots where they integrated it. Conclusion: Not only will there be a sustainable and successful method of controlling the nematodes that will be the combination of locally obtained fungi and crop rotation, but such collaboration will ensure that the use of pesticides in the management of nematodes is eliminated as well. The technique enhances production of crops and imparts a lasting soil suppressiveness, which can give the Iraqi farmers an alternative to chemicals in the long run. In the future, there is a need to improve the application procedures for scaling up at the regional levels.